Estudo de Grafeno mono e bi-camada sob deformação uniaxial por espalhamento Raman ressonante - Amanda Olinda Oliveira Coimbra (2013)
In this work we studied the effect of uniaxial strain on the eletronic and vibrational properties of monolayer and bilayer graphene using the experimental technique of Resonant Raman spectroscopy. The resonance Raman spectroscopy consists of sending a monochromatic light with differente wavelenghts on a material and analyze the spectrum of the backscattered light, obtaining information about the eletronic structure and vibrational properties of the material. Especially in the case of graphene, due to the shape of the dispersion curve close to the point e K, the Resonant Raman spectroscopy provides information about the electronic structure of the material near the Dirac point. In the Raman spectrum of graphene we analyze the region of the G (1580 cm1) and G0 (2700 cm1) bands characteristics of graphitic materials. As mechanical stress is applied in the sample, we observe the splitting of the G band and the dispersive behavior of the G0 band for different laser excitation energies. Besides that we obtained information about how the slope of the eletronic dispersion of this material varies with deformation, that in the case of the monolayer graphene, is related with the Fermi velocity of the material.